Effects of Feather-Pecking Phenotype on Physiological and Neurobiological Characteristics and Gut Microbiota Profile of Goslings - Mingfeng Wang; Yujiao Guo; Zhengfeng Cao; Qi Xu; Guohong Chen; Yang Chen (Animals)
FP is a detrimental behavior for chickens, ducks, and geese associated with numerous physiological and neurobiological characteristics, which have been identified in many species as regulated by the gut microbiota. However, it is unknown whether and how gut microbiota influences FP by regulating neurotransmitter systems in geese. This study aimed to investigate the phenotypic correlation between feather pecking and changes in physiological, neurobiological, and gut microbiota profiles in gosling. Three behavioral phenotypes were observed in goslings, including severe feather peckers (SFPs), victims of SFPs, and non-peckers (NFPs). The significantly lower feather scores and body weights were observed in victims compared to both SFPs and NFPs (p < 0.05). Regarding the physiological phenotype, victims had higher dopamine (DA) levels than NFPs, and SFPs had lower 5-hydroxytryptamine (5-HT) in the serum than NFPs (p < 0.001), with intermediate 5-HT levels in victims. Victims had lower glutathione peroxidase (GSH-Px) compared to SFPs and NFPs (p < 0.05). Moreover, higher mRNA expression levels of HTR1A, SLC6A4, and TPH2 in the 5-HT metabolic pathway were detected in NFPs than those in SFPs and victims (p < 0.05). In addition, regarding gut microbiota measured by 16S rRNA sequencing, SFPs had lower diversity and comparable cecal microbiota compared to victims and NFPs. Proteobacteria, Verrucomicrobia, Ruminococcus spp., and Bilophila spp. were enriched in SFPs, while Bacteroides and Parabacteroides were enriched in NFPs. From the predicted bacterial functional genes, the cAMP signaling pathway, cGMP–PKG signaling pathway, and pyruvate metabolism were activated in SFPs. The correlation analysis revealed that the genera Bacteroides spp. were associated with differences in 5-HT metabolism between the SFPs and NFPs. In summary, differences in the cecal microbiota profile and 5-HT metabolism drive FP phenotypes, which could be associated with the reduced gut abundance of the genera Bacteroides spp.